Variational analysis and full stability of optimal solutions to constrained and minimax problems. (July 2015) - Mordukhovich, Boris S.; Sarabi, M. Ebrahim
Abstract: The main goal of this paper is to develop applications of advanced tools of first-order and second-order variational analysis and generalized differentiation to the fundamental notion of full stability of local minimizers of general classes of constrained optimization and minimax problems. In particular, we derive second-order characterizations of full stability and investigate its relationships with other notions of stability for parameterized conic programs and minimax problems. Furthermore, the developed variational approach allows us to largely unify and provide new self-contained proofs of some quite recent results in this direction for problems of constrained optimization with C 2 -smooth data.